Pelatihan Penerapan Jurnal Dialog Di Kelas Bagi Para Guru Bahasa Indonesia di Kabupaten Cianjur - Maolida, Elis; Maryam, Siti (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
One of obstacles in language teaching and learning is less communication and interaction between teacher and students. Even though the interaction of sharing and receiving material can be carried out in classroom context, its limited intensity can hinder the exploration of students’ creativity. Besides, for specific learning material such as writing and literary appreciation, the students need to be facilitated to develop ideas, creativity, and expression in responding the content of material. In this case, dialogue journal can be an alternative technique in Indonesian language classes to improve students’ creativity in responding and appreciating the text. This motivates us to conduct a community service through teachers’ training to take advantages of dialogue journal for language class in various contexts. This training was part of community service series,”Multiliterasi bagi penguatan profesionalisme guru”. The activities were conducted virtually via Zoom, WhatsApp group, and content access through Gdrive. In this community service, the participants show positive responses by enthusiastically getting involved in the training. In addition, an interview to the participants show that they comprehend the material and can design dialogue journal activity for their class.